Analysis of the impact of financial inclusion on enhancing the activity of the Iraqi banking sector for the period 2017-2024 - Dakhil, Prof.Dr.Taher Risan Dakhil; Attia, Asst.Prof.Dr.Karrar Hatem Attia (Sulaimani Journal for Humanities, 2026)
The importance of financial inclusion lies in supporting economic development, as financial inclusion has become a goal that central banks seek to achieve, and thus enhance the activity of the banking sector by increasing the number of banking services and increasing the number of users of these services at the lowest possible cost. The research aims to measure the impact of financial inclusion indicators on enhancing the activity of the Iraqi banking sector. To achieve the research objective, annual data for the Iraqi banking sector for the period (2017-2024) were used. The research problem was formulated, which refers to the following question (Do financial inclusion indicators affect enhancing the activity of the Iraqi banking sector?) To test the research hypothesis, the EViews program was used to measure the impact of the independent variable (financial inclusion) represented by its indicators (banking density, banking spread, and ATM spread), on the dependent variable (enhancing banking sector activity) represented by its indicators (total volume of deposits, total volume of loans). The research reached a set of results, the most important of which is the existence of a statistically significant impact relationship between financial inclusion indicators (X1,X2, X3) and indicators of enhancing the activity of the Iraqi banking sector (Y1, Y2) at a significance level of (0.05). The current research recommends the necessity of providing electronic banking infrastructure, increasing banking awareness among all members of society, especially those who suffer from financial exclusion, as well as increasing the number of banking branches, and increasing ATM machines with the aim of increasing bank deposits, and then granting more bank credit to reach the development of the Iraqi banking sector
Keywords: financial inclusion; revitalizing the Iraqi banking sector